Analisis Efektifitas Multimedia Interaktif Dalam Menghadapi Tantangan Pendidikan di Era Globalisasi Industri 4.0 - Kurniawti, Annisa; Festiyed, Festiyed; Asrizal, Asrizal (Jurnal Penelitian Pembelajaran Fisika, 2019)
Interactive multimedia provides a very important role in the learning process because using interactive multimedia can motivate students to learn so that ultimately learning objectives can be achieved as desired and can help students in facing educational challenges in the era of industrial globalization 4.0. This research was conducted with a descriptive method with a quantitative approach. The purpose of this research is to analyze the effectiveness of interactive multimedia to improve learning outcomes, scientific literacy, and critical thinking skills of students in facing the challenges of education in the era of industrial globalization 4.0. The sample in this study was 5 (five) national journals that used interactive multimedia at the junior and senior high school level. The results of this study are: 1) interactive multimedia is most effectively used to improve student learning outcomes at the junior high school level; 2) interactive multimedia is most effectively used to improve students' critical thinking skills at the high school level, and 3) interactive multimedia is more effectively used at the junior secondary level and not at the senior secondary level in facing educational challenges in the era of industrial globalization 4.0